Ocular findings in MELAS syndrome – a case report - Modrzejewska, Monika; Chrzanowska, Martyna; Modrzejewska, Anna; Romanowska, Hanna; Ostrowska, Iwona; Giżewska, Maria (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
We present a case of a child with MELAS syndrome (mitochondrial encephalo-myopathy with lactic acidosis and stroke-like episodes), discussing clinical manifestation, ocular findings and diagnostic challenges. Predominant ocular symptom was a transient complete visual loss, while the predominant ocular sign was a visual field defect. The diagnosia was based on clinical manifestation, laboratory tests, brain scans and genetic testing which confirmed the pathognomonic mutation in the MTTL1 gene encoding the mitochondrial tRNA for leucine 3243> G. Ocular examination demonstrated decreased visual acuity (with bilateral best corrected visual acuity of .1). Periodical, transient visual loss and visual field defects were clinically predominant. Specialist investigations were carried out, which demonstrated homonymous hemianopia (kinetic perimetry), bilateral partial optic nerve atrophy (RetCam). Funduscopy and electrophysiology mfERG study did not confirm features of retinitis pigmentosa. The brain scans revealed numerous small cortical ischemic lesions within the frontal, parietal and temporal lobes, post-stroke focal areas within the occipital lobes and diffuse calcifications of the basal ganglia. During several years of follow-up, visual field defects showed progressive concentric narrowing. The patient received a long-term treatment with arginine, coenzyme Q and vitamin D, both oral and intravenous, but no beneficial effect for the improvement of ophthalmic condition was observed. As it is the case in severe MELAS syndrome, the course of disease was fatal and the patientdied at the age of 14.